2013
DOI: 10.1371/journal.pone.0057533
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chloroplast Genome Sequences of Mongolia Medicine Artemisia frigida and Phylogenetic Relationships with Other Plants

Abstract: Background Artemisia frigida Willd. is an important Mongolian traditional medicinal plant with pharmacological functions of stanch and detumescence. However, there is little sequence and genomic information available for Artemisia frigida, which makes phylogenetic identification, evolutionary studies, and genetic improvement of its value very difficult. We report the complete chloroplast genome sequence of Artemisia frigida based on 454 pyrosequencing.Methodology/Principal FindingsThe complete chloroplast geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
107
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 77 publications
10
107
2
Order By: Relevance
“…Previous studies have reported that A. gmelinii and A. capillaris contain useful metabolites with various pharmacological effects such as anti-infective and anti-oxidant activity and hepatoprotective and antifibrotic effects (K€ oncz€ ol et al 2012;Wang et al 2012). However, to date, genetic and genome research related to barcoding system lack in Artemisia genus, despite the importance of herbal medicine authentication system is increased (Liu et al 2013;Lee et al 2016). In this study, we Figure 1.…”
Section: Main Textmentioning
confidence: 71%
See 1 more Smart Citation
“…Previous studies have reported that A. gmelinii and A. capillaris contain useful metabolites with various pharmacological effects such as anti-infective and anti-oxidant activity and hepatoprotective and antifibrotic effects (K€ oncz€ ol et al 2012;Wang et al 2012). However, to date, genetic and genome research related to barcoding system lack in Artemisia genus, despite the importance of herbal medicine authentication system is increased (Liu et al 2013;Lee et al 2016). In this study, we Figure 1.…”
Section: Main Textmentioning
confidence: 71%
“…The highquality paired end sequences of 2.1 and 1.6 Gb were generated from A. gmelinii and A. capillaris, respectively, and separately assembled using CLC genome assembler (v. beta 4.6, CLC Inc., Lyngby, Denmark). Afterwards, contigs representing chloroplast sequence were retrieved, ordered and combined into a single draft sequence by comparing chloroplast genomes of A. frigida (JX293720, Liu et al 2013) and A. fukudo (KU360270, Lee et al 2016). The complete genome of A. gmelinii and A. capillaris were deposited in GenBank (A. gmelinii: KU736962 and A. capillaris: KU736963).…”
Section: Main Textmentioning
confidence: 99%
“…We isolated DNA from leaf tissues and performed whole genome shotgun sequencing using an Illumina Miseq platform (Illumina, San Diego, CA). High-quality paired end reads of 1.2 Gb were assembled using CLC genome assembler 4.6 (CLC Inc., Aarhus, Denmark) and contigs representing chloroplast sequence were retrieved, ordered, and combined into a single sequence, by the guidance of chloroplast genome of A. frigida (JX293720) (Liu et al 2013).…”
Section: Mitogenome Announcementmentioning
confidence: 99%
“…The expansion and contraction of IR are common evolutionary events in plants (Liu et al, 2013). It is believed that the locations of SSC/IR and LSC/IR junctions are markers of chloroplast genome evolution (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%